O papel político da imprensa batista: o Batista Paulistano e os governos de Jânio a Médici - Brito Júnior, Elias Bernardo de (2009)
The Brazilians Baptists settled down in the national territory at the end of 19th century, proceeding from The United States of America. Here, in Brazil, they have experienced a period of great growth. Today they are located in all the units of the federation. Its expansionism has awakened the need to create means of communication that kept the immense group cohesive. The Brazilians Baptists of the State of Sao Paulo founded the Batista Paulistano periodical in 1909. The periodical had an informative mark, it divulged the activities developed and it was the mean of communication between the leadership and the members in the State. This project investigates the political role of the Batista Paulistano periodical from Jânio government to Medici government. Period that marks the transition from a democratic regime of duty for a dictatorial regime implanted by Brazilian arm. This project seeks analyze whether the official adopted a posture of impartiality or a political engagement in the fight against military dictatorship. In addition to recognize the importance of the periodical as an historic document revealing of the quotidian , Cosmovision and Baptist Thought